RETRACTED: The Association Between Diet and Cardio-Metabolic Risk on Cognitive Performance: A Cross-Sectional Study of Middle-Aged Australian Adults - Gauci, Sarah; Young, Lauren M.; Arnoldy, Lizanne; Scholey, Andrew; White, David J.; Lassemillante, Annie-Claude; Meyer, Denny; Pipingas, Andrew (Frontiers in Nutrition, 2022)
Adherence to different dietary patterns has been linked the development of cognitive decline; yet little is known about whether this relationship is present in middle age. The current study aimed to explore the relationship between different dietary patterns, cognitive performance, and potential cardio-metabolic mechanisms for this relationship. Participants were recruited using a diet screening tool to ensure the cohort had a range of diet quality ranging from relatively poor to relatively healthy. In a sample of 141 middle aged adults (age: M = 52.84 years, SD = 6.87 years), multiple 24 h diet recalls were collected and used to score adherence to the Mediterranean diet, DASH (Dietary approaches to stop hypertension) diet and MIND (Mediterranean-DASH diet intervention for neurodegenerative delay) diet. Metabolic risk was assessed using the metabolic syndrome severity score (MetSSS) and arterial stiffness. Cognitive performance was assessed using the Swinburne University Computerized Cognitive Assessment Battery (SUCCAB). Adherence to the MIND diet was significantly related to Stroop Processing domain (β = .19, p = .035). None of the dietary patterns were significantly related to MetSSS or arterial stiffness. However, adherence to the DASH diet was significantly associated with two cardio-metabolic measures including lower augmentation index (β = -.17, p = .032) and lowered cholesterol (β = -.18, p = .041). Interestingly, two cardio-metabolic risk factors were also associated with better cognitive performance: MetSSS (β = .21, p = .010) and waist circumference (β = .22, p = .020). Together these findings suggest that diet in middle age may be important for cognitive functioning and cardio-metabolic risk. However, more research is needed in the form of randomized controlled trials to confirm the direction of these relationships.